Integrating a life course perspective in work environment and health research: empirical challenges and interdisciplinary opportunities - Ute Bültmann; Karin Broberg; Jenny Selander (Nordic Association of Occupational Safety and Health (NOROSH), 2024)
A healthy working life is fundamental for individuals and society. To date, increasingly research connects the earlier, pre-working life to later working life experiences and beyond, recognizing that a worker's health and exposure starts before the working life begins. The research, however, often lacks a fundamental understanding of (i) the underlying mechanisms and pathways accounting for differences in different life stages and (ii) the role of the social environment in shaping working life experiences. By integrating a life course perspective in our research and crossing disciplinary borders in rigorous, collaborative research, we may get a better understanding of the complex and dynamic interplay between work, environment and health. A life course perspective for work environment and health research A life course perspective in work environment and health research emphasizes the importance of prior life experiences, including the environments in which individuals were raised and exposed, their familial and educational backgrounds, and their physical and mental health status before entering the workforce (1, 2). Life course research in different disciplines has been instrumental in developing more robust causal models (3, 4), particularly for understanding developmental health trajectories and socioeconomic health inequalities (eg, 5-7). Adopting an interdisciplinary life course perspective in work environment and health research helps researchers answering questions as to whether and how the timing, duration, intensity, and context of past and present exposures (ie, pre-working, working, and non-working exposures) are associated with later life work and health outcomes. For instance, the 'exposome paradigm' is a concept used to describe the sum of occupational and environmental exposures an individual encounters throughout life, and how these exposures impact biology and health (8). In exposome research, a broad range of genetic, biological, chemical, physical, social and lifestyle factors is examined throughout the life course to provide a comprehensive picture of potential risk factors impacting working life health (9). In exposome research and beyond, it is important to examine how the exposure-outcome relationships are shaped by specific social, cultural and historical contexts (2). The conceptual framework of the 'Social Exposome' may help to integrate the social environment in conjunction with the physical environment into the exposome concept (10). Moreover, focusing on both historical and contemporary contexts is essential not only for advancing research but also for informing policy and practice, for example by identifying entry points for interventions. Exposures during the life course During the individual's life course, several vulnerable time windows for the impact of a multitude of exposures that potentially harm, protect or promote health, eg, occupational, environmental and social, can be distinguished. The (combinations of) exposures may operate in different life stages and contexts and - directly or indirectly via intergenerational transmission - contribute to health (figure 1). The individual may be particulary sensitive to harmful exposures or adverse experiences during developmental life stages, ie, pre/perinatal, childhood, adolescence, pregnancy and menopause/andropause. Other life stages may reflect vulnerable time windows due to a clustering of exposures, eg, work and family demands during parenthood, or an accumulation of exposures during the (working) life course at retirement and post-retirement age. As illustrated in figure 1, occupational exposure(s) can be divided in exposure through the parents' exposure (early in life) and an individuals' own exposure (later in life). Already in the pre/perinatal life stage, occupational exposure starts through the intergenerational transmission of the parents' occupational exposures. Current and bioaccumulated occupational exposure of chemicals and particles in the father at the time of conception can affect sperm quality. Together with the mother's exposure to occupational exposures of chemicals and particles prior to conception - or chemicals, particles, physical factors, ergonomic load, organizational and (psycho-)social conditions at work during pregnancy - this may affect fetal development and later disease development during the child's life course (11-15). During childhood, the growing child is exposed to parental occupational exposure(s), directly through chemicals and particles in the work clothes and skin or indirectly through organizational and psychosocial factors in the work environment that may increase the risk for mental and physical health problems in parents, which in turn may affect their parental rearing quality (16, 17). During adolescence and early adulthood, individuals usually encounter their first direct occupational exposures through their first (student) job or jobs. Already from this life stage, occupational exposures may accumulate during the (working) life course and may affect not only the active working life but also the post working life. Also important to note is that brain plasticity is not limited to childhood, adolescence or young adulthood as it persists throughout life. Some studies indicate that high physical and chemical exposure during this life stage, can increase the risk of disease later in life (18). A poor psychosocial school or work environment in younger years may also increase the risk of adverse labour market outcomes and mental health problems later in life (19, 20). In adulthood, men and women often start with (the planning of) family formation. Some occupational exposures affect fecundability, others can increase the risk of pregnancy-related disease, such as preeclampsia, hypertension or diabetes, or affect the offspring (21, 22). Chemicals, heat and stress-related exposures affect the ability to conceive. During pregnancy, the bodily and mental systems are vulnerable with changes in the endocrine and inflammation response that can dysregulate the HPA-axis, resulting in a prolonged stress response. The placenta can filter out many hazards, but not all toxicants, such as methylmercury and arsenic (23, 24). Physical exposure, such as noise and vibration, but also shift and night work can affect the womb and cause fetal growth restriction, preterm birth, and hearing impairment (eg, 12, 13, 25-27). During parenthood, occupational exposures may affect the parents' (mental) health and work-family balance (28, 29). Many chemical and physical exposures have now manifested in disease, eg, allergy, asthma and musculoskeletal diseases (28). During menopause in women, with a drastic decrease in oestrogen, and the slow testosterone decline in men (sometimes referred to as andropause), dysregulations of the hormone system may disrupt and affect the individual's susceptibility for occupational exposures in a way similar to environmental exposures (30). Towards retirement, the total cumulative occupational exposure burden over the working life course and the current exposure will affect the ability to stay at work and in the labor market. Post retirement, most direct occupational exposures have ceased, but others may have (bio-) accumulated over time and may cause health problems that manifest after retirement (31, 32). Along with occupational exposures, a multitude of other exposures are present during the entire life course that may operate across different contexts to contribute to health (see figure 1). For instance, chemical, physical and social stressors during the life course leave traces ('memories') on the molecular and tissue levels that may affect later life health (33). Epigenetic marks act as heritable memories in the cell as they respond to different endogenous and exogenous signals and can be propagated from one generation of cells to the next generation of cells (33). Next to the epigenetic marks, the social environment and social determinants of health during the life course, eg, socio-economic and lifestyle factors, social relationships, social cohesion and support, are known to impact health and add to the multitude of exposures to be examined, among others in conjunction with the environmental exposome (eg, 34).